Symmetry breakdown of electron emission in extreme ultraviolet photoionization of argon. Issue 1 (December 2018) - Ilchen, M.; Hartmann, G.; Gryzlova, E.; Achner, A.; Allaria, E.; Beckmann, A.; Braune, M.; Buck, J.; Callegari, C.; Coffee, R.; Cucini, R.; Danailov, M.; et al.
Abstract Short wavelength free-electron lasers (FELs), providing pulses of ultrahigh photon intensity, have revolutionized spectroscopy on ionic targets. Their exceptional photon flux enables multiple photon absorptions within a single femtosecond pulse, which in turn allows for deep insights into the photoionization process itself as well as into evolving ionic states of a target. Here we employ ultraintense pulses from the FEL FERMI to spectroscopically investigate the sequential emission of electrons from gaseous, atomic argon in the neutral as well as the ionic ground state. A pronounced forward-backward symmetry breaking of the angularly resolved emission patterns with respect to the light propagation direction is experimentally observed and theoretically explained for the region of the Cooper minimum, where the asymmetry of electron emission is strongly enhanced. These findings aim to originate a better understanding of the fundamentals of photon momentum transfer in ionic matter. Exploring the photoionization process leads to better understanding of the fundamental interactions between light and matter. Here the authors show the non-dipole contribution in the form of asymmetric photoelectron angular distribution from the ionization of argon atoms and ions.